For a Critique of Progressivism - Villalobos-Ruminott, Sergio (Re-presentaciones: Periodismo, comunicación y sociedad, 2023)
This article elaborates a critique of the distinctive progressivism of the contemporary Latin American left. For this purpose, we first interrogate the so-called populist reason developed by Ernesto Laclau, whose contributions constitute the most sophisticated and systematic version of a theory of politics capable of thinking about processes of democratic radicalization, beyond the hermeneutical framework of the Cold War. Once the potentialities and limitations of said populist reason have been pointed out, we proceed to interrogate political progressivism considering the Chilean case, precisely because it was in that country where neoliberalism was first implemented, manu militari, and where there was also a transition to democracy considered as an exemplary process by contemporary progressivist discourse. This will allow us, finally, to address the inability of progressivism to understand the sui generis character of social revolts, which tend to be criminalized by the official discourse of security and order, hallmarks of neoliberal governmentality